PERTANGGUNGJAWABAN HUKUM TRAVELOKA SEBAGAI PELAKU USAHA DALAM FENOMENA PEMBATALAN TIKET SEPIHAK TERHADAP KONSUMEN - ShintaDevia Giartika Gunawan (Bureaucracy Journal : Indonesia Journal of Law and Social-Political Governance, 2023)
Technological advances make it easier for humans to carry out their activities via the internet. One of them is the emergence of the Traveloka application which functions as a ticket booking application for various purposes, such as airplane tickets, hotel tickets, and tourism. Even though it is quite successful, there have been many cases of consumers getting unpleasant service from Traveloka. One of the problems most experienced by consumers is the unilateral cancellation of tickets by Traveloka business actors. Based on this, this research will analyze the form of legal liability from Traveloka against ticket cancellation unilaterally. This study uses normative research based on conceptual areas that use library research such as books, journals, and laws and regulations related to the object of research. The results of the study show that in the case of unilateral ticket cancellation, Traveloka acts as a business actor who is burdened with responsibility because they are deemed not to have fulfilled their obligations. Regarding ticket cancellation unilaterally, Traveloka as a business actor can be said to have committed a default